THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN RAISING PUBLIC AWARENESS OF PROPHETIC MEDICINE - Ridwan, Iwan; Maimunah, Ni'mah; Fathurrizqi, Haikal; Syathybie, Aca (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping the mindset, attitudes, and behavior of society based on Islamic values, including in terms of maintaining health and treatment. One important aspect that is often overlooked in IRE studies is the introduction to the concept of Thibbun Nabawi or the Prophet's medicine. This study aims to analyze how Islamic religious education contributes to increasing public awareness and understanding of the values of medicine taught by the Prophet Muhammad SAW, as well as how it is implemented in everyday life. The research method used is library research with a descriptive qualitative approach, which examines various Islamic literature, hadith, and relevant scientific works. The results of the study show that Islamic religious education not only plays a role in shaping spiritual piety, but also serves as an important instrument in fostering holistic awareness of the importance of physical and spiritual health. Through the integration of Thibbun Nabawi material into the curriculum, lectures, and da'wah activities, the community has gained a better understanding that maintaining health is part of worship and a divine mandate. Values such as balance, cleanliness, consumption of halal and thayyib food, as well as prayer-based and herbal medicine, can strengthen the community's paradigm of the Prophet's medicine as a solution. Thus, Islamic religious education plays a significant role in internalizing the Prophet's teachings on health into the culture of Muslims in a sustainable manner.